International housing markets, unconventional monetary policy and the zero lower bound - Florian Huber; Maria Teresa Punzi (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2016)
In this paper we propose a time-varying parameter VAR model for the housing market in the United States, the United Kingdom, Japan and the Euro Area. For these four economies, we answer the following research questions: (i) How can we evaluate the stance of monetary policy when the policy rate hits the zero lower bound? (ii) Can developments in the housing market still be explained by policy measures adopted by central banks? (iii) Did central banks succeed in mitigating the detrimental impact of the financial crisis on selected housing variables? We analyze the relationship between unconventional monetary policy and the housing markets by using the shadow interest rate estimated by Krippner (2013b). Our findings suggest that the monetary policy transmission mechanism to the housing market has not changed with the implementation of quantitative easing or forward guidance, and central banks can affect the composition of an investor's portfolio through investment in housing. A counterfactual exercise provides some evidence that unconventional monetary policy has been particularly successful in dampening the consequences of the financial crisis on housing markets in the United States, while the effects are more muted in the other countries considered in this study.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: C32; E23; E32; 330; Zero Lower Bound; Shadow interest rate; Housing Market; Time-varying parameter VAR